Design patterns in C♯ - Metsker, Steven John (Software patterns series., 2004)
Steven John Metsker explains how to use C# as an object-oriented language, using design patterns to create clean code while taking advantage of the extensive Microsoft(R) .NET Framework Class Libraries. For all 23 classic "Gang of Four" design patterns, Metsker offers detailed code examples utilizing C# and the .NET Framework--as well as programming exercises crafted to help you rapidly build expertise. His exercises and explanations make extensive use of the Unified Modeling Language, helping you build your skills in this standard notation. Design patterns covered include: Interfaces: Adapter, Facade, Composite, and Bridge Responsibility: Singleton, Observer, Mediator, Proxy, Chain of Responsibility, and Flyweight Construction: Builder, Factory Method, Abstract Factory, Prototype, and Memento Extensions: Decorator, Iterator, and Visitor If you've already used design patterns in other languages, Design Patterns in C# will deepen your understanding, build your confidence, and help you apply them to any C# project. If you're a Microsoft programmer who's new to design patterns, this book will be an ideal practical introduction. www.awprofessional.com/patterns/ ADDISON-WESLEY PROFESSIONAL Pearson Education ISBN: 0-321-12697-1